Threaded Intramedullary Nails Are Biomechanically Superior to Crossed K-wires for Metacarpal Neck Fractures. (January 2023) - Patel, Midhat; Castañeda, Paulo; Campbell, David H.; Putnam, Jill G.; McKee, Michael D.
Background: Intramedullary nail (IMN) fixation of metacarpal fractures is an alternative to Kirschner wire (K-wire) fixation. The goal of this study was to compare the biomechanical properties of K-wire fixation with a threaded IMN (InNate; ExsoMed, Aliso Viejo, California). Methods: The study design was based on previously described biomechanical models for evaluating metacarpal fractures. Sixteen fresh frozen small finger–matched and ring finger–matched pairs were randomized to either IMN or 0.045 in K-wire fixation after receiving a standardized neck osteotomy. Proper implant placement was confirmed with plain radiographs. Specimens then underwent loading in a 3-point bend configuration. Load to failure (LTF), stiffness, and fracture displacement were recorded. Mechanical failure was defined by a sharp change in the load-displacement curve. Results: Age, sex, sidedness (left or right), and digit (ring or small finger) were evenly distributed between groups. The IMN had a significantly higher LTF than K-wires (546 N vs 154 N, P < .001). The K-wire fixation demonstrated plastic deformation between 75 and 150 N. Intramedullary nail stiffness was higher than that of K-wires (155.89 N/mm vs 59.28 N/mm, P < .001). Conclusions: When surgical fixation is indicated for metacarpal neck and shaft fractures, the threaded IMN is biomechanically superior to crossed K-wires with the application of 3-point bend.